Identyfikacja różnic indywidualnych w analizie Procrustesa - Zaborski, Artur (Identification of individual differences in procrustes analysis, 2006)
The paper presents Procrustes analysis in which several given coordinate matrices are fit to each other in such a way that uninformative differences are eliminated and an optimal average configuration (group space) is formed. In Procrustes analysis individuals are represented as points in the space of weights. The dimensional weights may be interpreted as expressions of the different importance that individual k attaches to the dimensions of the group space.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 492-500